PERAN HUKUM ACARA PIDANA DALAM MENJAMIN KEADILAN PADA PROSES PENYIDIKAN TINDAK PIDANA DI POLRES PADANGSIDIMPUAN - Azmi Hannum Hasibuan, Lenni Putri (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2025)
The Criminal Procedure Code Number 8 of 1981 concerning the Criminal Procedure Code states that before conducting an investigation, an investigation is first carried out because it is one of the methods or methods or sub-functions of the investigation that precedes other actions, namely enforcement in the form of arrest, detention, search, confiscation, examination of letters, summonses, examination of examinations, and submission of files to the public prosecutor. The research method used is empirical legal research. The results of the study show that in the investigation process, investigators must really apply the criminal procedure law in order to ensure justice for the parties involved, and improve the quality of the police in the investigation level, it is good for the police to apply the principles of justice to the parties involved in the criminal investigation process.